A structure activity relationship for ring closure reactions in unsaturated alkylperoxy radicals. Issue 31 (27th July 2021) - Vereecken, L.; Vu, G.; Wahner, A.; Kiendler-Scharr, A.; Nguyen, H. M. T.
Abstract : The ring closure in unsaturated alkyl peroxy radicals can be a competitive process in the atmospheric oxidation of biogenic organic compounds. Abstract : Terpenoids are an important class of multi-unsaturated volatile organic compounds emitted to the atmosphere. During their oxidation in the troposphere, unsaturated peroxy radicals are formed, which may undergo ring closure reactions by an addition of the radical oxygen atom on either of the carbons in the CC double bond. This study describes a quantum chemical and theoretical kinetic study of the rate of ring closure, finding that the reactions are comparatively fast with rates often exceeding 1 s −1 at room temperature, making these reactions competitive in low-NOx environments and allowing for continued autoxidation by ring closure. A structure–activity relationship (SAR) is presented for 5- to 8-membered ring closure in unsaturated RO2 radicals with aliphatic substituents, with some analysis of the impact of oxygenated substituents. H-migration in the cycloperoxide peroxy radicals formed after the ring closure was found to be comparatively slow for unsubstituted RO2 radicals. In the related cycloperoxide alkoxy radicals, migration of H-atoms implanted on the ring was similarly found to be slower than for non-cyclic alkoxy radicals and is typically not competitive against decomposition reactions that lead to cycloperoxide ring breaking. Ring closure reactions may constitute an important reaction channel in the atmospheric oxidation of terpenoids and could promote continued autoxidation, though the impact is likely to be strongly dependent on the specific molecular backbone.